THE INFLUENCE OF PICTURE AND PICTURE MODEL ON INDONESIAN WRITING SKILLS - Mulyani, Linda; Solihat, Dadang; Hanifah, Ifah (Indonesian Journal of Learning and Instruction, 2018)
This study aims at determining the effect of the use of picture and picture model on Indonesian writing skills Â narration essay in the class IV A and IV B Elemetary School 1 Purwawinangun. The samples in this study are 49 students. The method used in this research is quasi experiment. Data collection techniques used in this study is an essay written test. Data analysis technique in this research is normality test, homogeneity test, t-test, and n-gain test. The result of pretest mean score of experimental and control class are 44.2 and 43.6. The result of posttest mean score of experimental and control class are 82.8 and 72.4. The result of the hypothesis test obtained the value of based on the t-test results obtained 0,000 significance level, where 0.000 0.05, it means that Ha accepted based on the acceptance criteria hypothesis and Ho rejected, that there is an effect of using Picture and Picture type cooperative model on narration essay writing skill of students. The result of the n-gain test is 0.7 indicating that there is an increase in the experimental group using the picture and picture type cooperative model with high criteria. So it can be concluded that there is influence of using of picture and picture type in cooperative model of students narration essay writing skills.Keywords:Â cooperative model; picture; writing skill; narration essay.